Optimisation of the export structure in transport companies: a case study - Shpak, Nestor; Dvulit, Zoriana; Maznyk, Liana; Sroka, Włodzimierz; Zaverbnyj, Andrij; Levchenko, Olha (My University, 2023)
With the increasing complexity of economic systems caused by the intensification of European integration processes and the general globalisation trend, the problems of ensuring the optimal operation of transport companies are becoming especially important. Given these facts, the article's purpose is to develop and test a structural modelling algorithm based on the system state indicator (entropy of the structure of the export freight system). Research methods used in the article include: statistical (structure and dynamics analysis), systematisation and comparison, system analysis methods (entropy characteristics), and mathematical programming methods. The mathematical formulation of problems involves studying structural uncertainty due to the synergistic influence of interconnected structures. As a result of the optimisation calculations, the entropy index decreased as a consequence of the optimisation of the studied structures of export cargo. The study results using structural-dynamic modelling provide an opportunity to determine benchmarks for optimising the structure of export transportation. Therefore, they can act as indicators in the relevant field to substantiate the performance of large transport and logistics companies. The use of such approaches will help improve cooperation on a shared basis between Ukraine and the countries of Central Europe. В умовах ускладнення економічних систем, викликаного активізацією євроінтеграційних процесів та загальною тенденцією глобалізації, проблеми забезпечення оптимальної роботи транспортних компаній набувають особливої ​​актуальності. Враховуючи ці факти, метою статті є розробка та тестування алгоритму структурного моделювання на основі індикатора стану системи (ентропії структури експортно-вантажної системи). У статті використовуються такі методи дослідження: статистичні (аналіз структури та динаміки), систематизації та порівняння, методи системного аналізу (ентропійні характеристики), методи математичного програмування. Математична постановка задач передбачає вивчення структурної невизначеності внаслідок синергетичного впливу взаємопов’язаних структур. У результаті оптимізаційних розрахунків показник ентропії зменшився як наслідок оптимізації досліджуваних структур експортних вантажів. Результати дослідження за допомогою структурно-динамічного моделювання дають можливість визначити орієнтири оптимізації структури експортних перевезень. Тому вони можуть виступати індикаторами у відповідній сфері для обґрунтування діяльності великих транспортно-логістичних компаній. Використання таких підходів сприятиме покращенню співпраці на спільних засадах між Україною та країнами Центральної Європи.
Keywords: кафедра економіки праці та менеджменту; export; freight transportation; ентропія; експорт; вантажні перевезення; вантажні перевезення